Paramyxovirus-1 in feral pigeons (Columba livia) in Ontario - Johnston, Kathleen M. (1992)
Paramyxovirus-1 (PMV-1) infection was diagnosed in racing pigeons in Ontario during 1985, but it was not until January 1989, that the virus was isolated from feral pigeons (Columba livia) in this province. During an 18 month period beginning January 1988, a total of 43 feral pigeons was submitted to the Wildlife Diseases Laboratory, Pathology Department, Ontario Veterinary College. A history of neurological signs accompanied most of the birds. Tissues from 29 birds were submitted for PMV-1 isolation. Allantoic inoculation of embryonated chicken eggs yielded PMV-1 in 10 of the pigeons submitted. On the basis of histological criteria, we believe that 12 other birds were also infected with PMV-1. Gross pathological changes were unremarkable. Lymphplasmacytic interstitial nephritis was observed histologically in all birds from which PMV-1 was isolated. Other lesions seen, in decreasing frequency of occurrence, were lymphoplasmacytic interstitial hepatitis and multifocal hepatic necrosis, lymphoplasmacytic interstitial pancreatitis, nonsuppurative encephalitis and myelitis. The existence of PMV-1 in feral pigeons poses a potential threat to the poultry population since there is ample opportunity for mingling with poultry under open housing management. There is also a concern that pigeons may harbor the virus, perhaps in the kidney, and become chronic carriers and potential long-term disseminators of the disease.